1993
DOI: 10.1111/j.1469-8986.1993.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for task effects on semantic priming in auditory word processing

Abstract: Event-related brain potentials (ERPs) associated with semantic relatedness were recorded in two auditory word recognition tasks. In the Memorize task, subjects listened to a list of words in anticipation of a subsequent recognition test. In the Count Nonwords task, subjects silently counted the number of nonwords occurring within a list of words. Within each list, target words were either semantically related or unrelated to the immediately preceding word. As in comparable visual tasks, the amplitude of a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
103
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 46 publications
13
103
1
Order By: Relevance
“…In the latter case, the past participle is presumably less constrained by the preceding context, so that more effort is required in order to activate the lexical item (Holcomb, 1993). This interpretation is consistent with a large number of studies in which it has been shown that the N400 is associated with the difficulty in integrating a lexical element in a semantically constraining sentence context (Bentin, Kutas, & Hillyard, 1993;Bentin, McCarthy, & Wood, 1985;Friederici et al, 1993;Kutas & Hillyard, 1984;Rosler, Friederici, Piitz, & Hahne, 1993). The results also indicate that the fast comprehenders used the semantically constraining information at this point in the sentence.…”
Section: Individual Differencessupporting
confidence: 71%
“…In the latter case, the past participle is presumably less constrained by the preceding context, so that more effort is required in order to activate the lexical item (Holcomb, 1993). This interpretation is consistent with a large number of studies in which it has been shown that the N400 is associated with the difficulty in integrating a lexical element in a semantically constraining sentence context (Bentin, Kutas, & Hillyard, 1993;Bentin, McCarthy, & Wood, 1985;Friederici et al, 1993;Kutas & Hillyard, 1984;Rosler, Friederici, Piitz, & Hahne, 1993). The results also indicate that the fast comprehenders used the semantically constraining information at this point in the sentence.…”
Section: Individual Differencessupporting
confidence: 71%
“…Among these, we focused our analyses in the temporal windows encompassing three components known to be associated with orthographic, phonological, and semantic analyses of words. Most previous reports had suggested the effects of attention on language are limited to processing taking place late in time, around 400 msec, centered in the N400 component Bentin et al, 1993Bentin et al, , 1995Holcomb, 1988), or in the 300 msec range, when tasks stressed phonological processing (Proverbio, Vecchi, & Zani, 2004;Bentin et al, 1999). Earlier stages related to orthographic processing had mostly been considered to take place in a common manner, irrespective of task demands (Maurer, Brandeis, & McCandliss, 2005;Bentin et al, 1999;Allison, McCarthy, Nobre, Puce, & Belger, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have manipulated the depth of word processing by means of task demands. For example, it has been shown that the amount of semantic priming, as indexed by the N400 effect (i.e., the difference in amplitude for related vs. unrelated semantic pairs) is significantly reduced when counting words compared to memorizing them (Bentin, Kutas, & Hillyard, 1993; see also Bentin Kutas, & Hillyard, 1995;Holcomb, 1988). The attentional blink also affects the brain correlates of word processing (Sergent, Baillet, & Dehaene, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, two ERP components appear sensitive to differing aspects of spoken word recognition: the N400, a component traditionally associated with semantic processing of spoken or written words (Bentin et al, 1993;Kutas and Hillyard, 1980), and an earlier occurring negativity, the Phonological Mapping Negativity (PMN), 1 which has been previously linked to phonological processes (Connolly et al, 1992(Connolly et al, , 1990. Though the N400 is typically associated with semantic analysis, there is a sizable literature showing that the N400 is also modulated by phonological factors (Dumay et al, 2001;Praamstra and Stegeman, 1993;Praamstra et al, 1994;Radeau et al, 1998;Rugg, 1984a,b).…”
Section: Introductionmentioning
confidence: 99%